Discussion about the similarity of the forms of the cities of Porto (Portugal) and Qazvin (Iran) - Jabbari, Mona (2014)
At present, in major cities, the lack of urban structure cohesion and connectivity promoted by the expansion of street network dominated by cars has increased dramatically. Hence, social life and citizen rights considering anthropocentric and human scale have been put at risk in many cities. â Old Townsâ are perceived as urban structures of the past that are revitalized and given new significance in contemporary cities. The geometrical order of the cities structures shape diverse urban tissue and promote the development in several directions. However, the main activities of the cities occur in the places with the most social interactions. In this context, this paper presents an ongoing research that aims to compare the main areas of Porto (Portugal) and Qazvin (Iran), based on growth of the cities around its historic center, i.e. â Old Townâ . The urban form of the cities will be analyzed and assessed by a methodology based on street pattern identification. Also will be discussed the urban design and environmental quality. Research findings shows that the main areas of the both cities require new pattern solutions in order to promote connectivity through pedestrian network.